A composite water repellent protective film and a method for manufacturing the same

CN122958840APending Publication Date: 2026-10-23SHENZHEN DIDAO MICROELECTRONICS TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611166587.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-08-12
Filing Date
2026-08-03
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

传统保护膜多采用单一的化学涂层材料,其拒水性能在复杂的半导体制造环境中难以持久保持,且与新型半导体材料的兼容性较差

Benefits of technology

[0053]本发明创新之处在于:本发明提供一种具有复合结构的拒水性保护膜,其采用支撑层与表面拒水层的复合设计,通过材料协同效应实现卓越的综合防护性能。支撑层采用聚合度梯度复配技术,其中低聚合度组分通过纳米级孔隙渗透实现高深宽比结构的高效填充,高聚合度组分提升对晶片微电路图案的支撑稳定性;表面拒水层枝接全氟丙烯酸酯,具有超低表面能和水接触角≥110°的特性。本发明通过结构协同解决单一材料性能不足的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a composite structure water-repellent protective film and a preparation method thereof, and comprises a supporting layer and a water-repellent layer. A dual-component high-low polymerization degree compound system is innovatively adopted, and short chains and long chains are cooperatively constructed in different mass ratios. The short chain component can realize efficient filling of high-depth-width-ratio microcircuit gaps due to low viscosity characteristics, and the long chain component endows the material with excellent mechanical properties, realizing the unity of high permeability and structural rigidity. The water-repellent layer adopts polymer chain segments modified by water-repellent functional groups, significantly reduces the wettability of the substrate surface, and endows the substrate surface with excellent water-repellency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor manufacturing and precision electronic device protection technology, specifically relating to a composite water-repellent protective film that can effectively prevent circuit pattern collapse and its preparation method. Background Technology

[0002] In fields such as networking and digital home appliances, semiconductor equipment is rapidly developing towards high performance, high functionality, and low power consumption. To meet this demand, the miniaturization of circuit patterns is constantly advancing. However, as the miniaturization of circuit patterns deepens, pattern collapse becomes increasingly prominent, becoming a key bottleneck restricting the development of semiconductor manufacturing. In the semiconductor equipment manufacturing process, the cleaning process accounts for 30-40% of the overall process, and its main purpose is to remove contaminants such as particles and metal impurities. However, with the miniaturization of semiconductor equipment circuit patterns, the aspect ratio of the patterns is constantly increasing. In the process after cleaning or rinsing, when the gas-liquid interface passes through the pattern, it is very easy to cause pattern collapse. Once pattern collapse occurs, it may not only require changes to the pattern design, but also lead to a significant reduction in production yield, seriously affecting production efficiency and product quality. Therefore, an effective solution is urgently needed.

[0003] Currently, forming a water-repellent protective film on the surface of a pattern has been proven to be an effective way to prevent pattern collapse. This method requires replacing the cleaning solution with a chemical solution for forming the water-repellent protective film while the pattern surface is not dry. For example, Japanese Patent Application Publication No. 2017-063179 discloses a surface treatment agent containing a silylating agent and a nitrogen-containing heterocyclic compound without silicon atoms, which can effectively prevent inorganic / resin patterns from collapsing. In addition, Chinese Patent Publication No. CN111742391A further proposes a chemical solution for forming a water-repellent protective film, which contains a silylating agent, a nitrogen-containing compound, and an organic solvent. By introducing a nitrogen-containing compound with a specific structure, the alkalinity adaptability of the catalyst is improved.

[0004] However, existing water-repellent protective films have many shortcomings. Traditional protective films mostly use a single chemical coating material, whose water-repellent properties are difficult to maintain for a long time in the complex semiconductor manufacturing environment, and they also have poor compatibility with new semiconductor materials. Although some protective films can reduce surface tension to a certain extent, they cannot provide sufficient structural support for circuit patterns with high aspect ratios, and still cannot effectively prevent pattern collapse. Therefore, it is necessary to develop a new type of water-repellent protective film that not only has excellent water-repellent properties but also enhances the structural protection of circuit patterns, fundamentally solving the problem of pattern collapse. Summary of the Invention

[0005] This invention addresses the shortcomings of existing technologies by providing a composite water-repellent protective film and its preparation method. Through unique material combinations and structural design, this invention significantly improves the water-repellent performance of the protective film, its ability to support and protect circuit patterns, and the filling rate of micro-gap circuits, effectively preventing pattern collapse. The invention also provides a preparation method for this protective film, ensuring uniform material composite and stable structural molding, enabling large-scale production. This provides an efficient and reliable pattern protection solution for the semiconductor manufacturing industry.

[0006] To achieve the above technical objectives, the present invention adopts the following technical solution: a composite water-repellent protective membrane, comprising a support layer and a water-repellent layer disposed on the surface of the support layer, wherein: (1) The support layer comprises a low-polymerization degree material (Ⅰ) and a high-polymerization degree material (Ⅱ). A-(B) i -C (Ⅰ) In structural formula (Ⅰ), B is a repeating unit selected from polycaprolactone segment (CH2)5−CO−O, polylactic acid segment CH(CH3)−CO−O, and polycarbonate segment O−C(=O)−O−R, where R is selected from aliphatic or aromatic groups; A and C are the head and tail groups of the molecular chain, selected from hydroxyl, carboxyl, amino, or methyl and ethyl groups; the degree of polymerization i ranges from 1 to 50. A-(B) m -C (Ⅱ) In structural formula (II), B is a repeating unit selected from polycaprolactone segment (CH2)5−CO−O, polylactic acid segment CH(CH3)−CO−O, and polycarbonate segment O−C(=O)−O−R, where R is selected from aliphatic or aromatic groups; A and C are the head and tail groups of the molecular chain, selected from hydroxyl, carboxyl, amino, or methyl and ethyl groups; the degree of polymerization m ranges from 51 to 200. (2) The water-repellent layer is obtained by grafting water-repellent monomers onto a high-polymerization-degree material (II), wherein the water-repellent monomers are selected from: perfluorohexyl acrylate, perfluorohexyl methacrylate, perfluorooctyl acrylate, perfluorooctyl methacrylate, perfluorodecyl acrylate, perfluorodecyl methacrylate, perfluorododecyl acrylate, perfluorododecyl methacrylate, perfluorotetradecyl acrylate, perfluorotetradecyl methacrylate, perfluorohexadecyl acrylate, perfluorohexadecyl methacrylate, perfluorooctadecyl acrylate, and perfluorooctadecyl methacrylate.

[0007] Preferably, the water-repellent monomer is selected from perfluorohexyl acrylate, perfluorooctyl acrylate, and perfluorodecyl acrylate.

[0008] Preferably, the repeating units in the low-polymerization-degree material (Ⅰ) and the high-polymerization-degree material (Ⅱ) are selected from polycaprolactone segments (CH2)5−CO−O.

[0009] Preferably, the mass ratio of the low-polymerization-degree material (Ⅰ) to the high-polymerization-degree material (Ⅱ) is in the range of 24:75 to 60:40.

[0010] The present invention also provides a method for preparing the above-mentioned composite structure water-repellent protective film, comprising the following steps: S1. Synthesis of polycaprolactone oligomers: Under nitrogen protection, ε-caprolactone monomer, organic solvent, initiator and catalyst were added to the reaction flask; the reaction flask was placed in an oil bath at 120℃±3℃ and reacted for 8-15 hours under nitrogen atmosphere and magnetic stirring. After the reaction was completed, the mixture was cooled to room temperature and the reaction was quenched by a small amount of glacial acetic acid / ethanol. Then, the mixture was quickly added dropwise to glacial methanol to precipitate the product. After standing and filtering, the precipitate was washed with methanol several times and dried to obtain a white solid polycaprolactone oligomer; the molar ratio of ε-caprolactone monomer to initiator was (55-75):1.

[0011] S2. Synthesis of polycaprolactone polymer: Under nitrogen protection, ε-caprolactone monomer, organic solvent, initiator and catalyst were added to the reaction flask; the reaction flask was placed in an oil bath at 120℃±3℃ and reacted for 8-15 hours under nitrogen atmosphere and magnetic stirring. After the reaction was completed, the mixture was cooled to room temperature and the reaction was quenched by a small amount of glacial acetic acid / ethanol. Then, the precipitate was rapidly added dropwise to glacial methanol, allowed to stand, filtered, and the precipitate was washed with methanol several times and dried to obtain a white solid polycaprolactone polymer; the molar ratio of ε-caprolactone monomer to initiator was (90-110):1.

[0012] S3. Synthesis of the water-repellent polymer: Under nitrogen protection, the polycaprolactone polymer and solvent were added to the reactor and stirred to dissolve. After stirring, the mixture was placed in an ice-water bath. The catalyst and bromine source were slowly added under stirring. After the addition was completed, the temperature was raised to 25±5℃ and the reaction was carried out for more than 12 hours. After the reaction was completed, the triethylamine bromide was removed by filtration. Then, the mixture was concentrated by rotary evaporation, precipitated with ice-cold methanol, and dried to obtain PCL-Br. S4. Under nitrogen protection, PCL-Br, water-repellent monomer and solvent are added to the reactor and stirred to dissolve. After deoxygenation by freeze pumping, catalyst is added and the reaction is stirred at 65±5℃ for at least 8 hours. After the reaction is completed, quencher is added to quench the reaction and catalyst is removed by passing through a neutral alumina column. After rotary evaporation and concentration, ice-cold methanol is added dropwise to precipitate and filter. The water-repellent layer material is then dried. S5. Weigh out polycaprolactone oligomer, polycaprolactone polymer, and water-repellent layer material in a molar ratio of (0.9-1.2):(0.9-1.2):(0.9-1.2), dissolve them in a solvent, and stir until completely dissolved to obtain a protective film composition solution. S6. The protective film composition solution is dropped onto the semiconductor substrate and spin-coated. After drying under reduced pressure, the protective film is cured and formed.

[0013] Preferably, in steps S1 and S2, which synthesize polycaprolactone oligomers and polycaprolactone polymers respectively, the initiator is selected from monohydroxy initiators, dihydroxy initiators, or polyhydroxy initiators; the monohydroxy initiators include methanol, ethanol, isopropanol, tert-butanol, n-hexanol, and benzyl alcohol; the dihydroxy initiators include ethylene glycol, 1,3-propanediol, 1,4-butanediol, dihexanediol, and terephthalic acid; the polyhydroxy initiators include glycerol, trimethylolpropane, pentaerythritol, and glucose, etc. Monohydroxy initiators are preferred.

[0014] 7. Preferably, in steps S1 and S2, the organic solvent is selected from anhydrous toluene, the catalyst is selected from stannous octoate, and the quencher is selected from glacial acetic acid and / or ethanol.

[0015] Preferably, in step S3, the solvent is selected from anhydrous dichloromethane and the bromine source is selected from 2-bromoisobutyryl bromide.

[0016] Preferably, in step S4, the solvent is composed of toluene and trifluorotoluene in a volume ratio of 1:1; and the catalyst is copper bromide CuBr and N,N,N',N'',N''-pentamethyldiethylenetriamine PMDETA.

[0017] Preferably, the solvent in step S5 is selected from: methanol, ethanol, tetrahydrofuran, dioxane, methyl cellosolve acetate, ethyl cellosolve acetate, ethyl acetoacetate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether. Propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol butyl ether acetate, toluene, xylene, methyl ethyl ketone, 4-hydroxy-4-methyl-2-pentanone, cyclopentanone, cyclohexanone, 2-heptanone, γ-butyrolactone, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone.

[0018] Preferably, the solvent in step S5 is selected from propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, dipropylene glycol methyl ether acetate, and propylene glycol butyl ether acetate.

[0019] Beneficial Effects: Compared with existing technologies, the water-repellent protective film of this invention achieves multiple protections for circuit patterns through a composite structure design of a support layer and a water-repellent layer. The support layer is composed of a blend of low-polymerization and high-polymerization materials. The low-polymerization material, with its shorter molecular chains, possesses excellent fluidity, allowing it to quickly penetrate and fill the fine trenches of high aspect ratio circuits in a very short time, achieving efficient filling. The high-polymerization long-chain molecules, due to their longer molecular chains, diffuse more slowly and accumulate near the outer region of high aspect ratio channels, forming a high-strength support structure. This effectively enhances the overall tensile strength of the film layer, enabling it to stably support the circuit pattern, uniformly disperse external forces, and significantly reduce stress concentration. The water-repellent coating repels water with extremely low surface energy, reducing direct contact between liquid and the pattern. The synergistic effect of the composite structure reduces the pattern collapse rate by more than 90% in simulated cleaning processes for high aspect ratio circuit patterns, greatly improving chip manufacturing yield. Detailed Implementation Plan

[0020] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. After reading the present invention, any modifications of the present invention in various equivalent forms by those skilled in the art will fall within the scope defined by the appended claims.

[0021] This invention provides a composite hydrophobic protective membrane, comprising: a support layer: innovatively employing a high- and low-polymerization-degree compound system, constructed synergistically by short and long chains in different mass ratios. The short-chain component, with its low viscosity, enables efficient filling of micro-circuit gaps with high aspect ratios, while the long-chain component imparts excellent mechanical properties to the material, achieving a balance between high permeability and structural rigidity; and a hydrophobic layer: employing polymer segments modified with hydrophobic functional groups. This layer and the underlying layer form a gradient transition structure through interfacial chemical bonding, ensuring interlayer bonding strength while maintaining superhydrophobic properties.

[0022] The following is a detailed description of the main components of the water-repellent protective film of the composite structure of the present invention: 1. The underlying support layer material is used to form a support structure on the surface of a wafer with a high aspect ratio circuit pattern, and mainly comprises a low-polymerization-degree material (Ⅰ) and a high-polymerization-degree material (Ⅱ), wherein: (1) Low-polymerization-degree materials, which have the following general structural formula, A-(B)iC(Ⅰ),In formula (Ⅰ), B represents a repeating structural unit, and different low-polymerization-degree polymers have different structures. The repeating unit can be: polycaprolactone segment (CH2)5−CO−O, polylactic acid segment CH(CH3)−CO−O, or polycarbonate segment O−C(=O)−O−R, where R is selected from aliphatic or aromatic groups, etc. These repeating structural units determine the basic chemical properties, physical properties, and molecular chain morphology of the material. i represents the degree of polymerization, and the specific value depends on the different material characteristics and application requirements. The value of i directly affects the molecular chain length, and thus affects the material's flowability, viscosity, and other properties. The preferred range for i is 1-50. For example, a lower i value results in a shorter molecular chain, better material flowability, and facilitates the filling of complex structures; a higher i value results in a longer molecular chain, providing a certain mechanical strength.

[0023] Here, A and C represent the beginning and end of the molecular chain, and their specific structure depends on the polymerization initiator used. The end groups can be active groups such as hydroxyl (-OH), carboxyl (-COOH), and amino (-NH2), or inert end groups such as methyl (-CH3) and ethyl (-C2H5). Active end groups can participate in subsequent crosslinking and grafting reactions, further optimizing material properties; inert end groups stabilize the molecular chain, preventing degradation or adverse reactions under specific conditions.

[0024] As a preferred example, in a specific instance of the above general formula (I), when using caprolactone for polymerization: different types of initiators can yield hydroxyl-terminated caprolactone, carboxyl-terminated caprolactone, and amino-terminated caprolactone, etc.; more preferably, a hydroxyl-containing initiator can be used. Examples of specific initiators include monohydroxy initiators such as methanol, ethanol, isopropanol, tert-butanol, n-hexanol, and benzyl alcohol; dihydroxy initiators such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, dihexanediol, and terephthalic acid; and polyhydroxy initiators such as glycerol, trimethylolpropane, pentaerythritol, and glucose. Monohydroxy initiators are even more preferred.

[0025] (2) High-polymerization-degree polymer materials have the same general structural formula as low-polymerization-degree materials, but the initiator used is preferably a monohydroxy initiator, which allows the polymer to have known and controllable grafting sites, providing active sites for subsequent modification with water-repellent functional groups. Compared with low-polymerization-degree materials, the degree of polymerization of polycaprolactone segments is preferably 51-200.

[0026] Preferred graft monomers for water-repellent grafting include: perfluorohexyl acrylate, perfluorohexyl methacrylate, perfluorooctyl acrylate, perfluorooctyl methacrylate, perfluorodecyl acrylate, perfluorodecyl methacrylate, perfluorododecyl acrylate, perfluorododecyl methacrylate, perfluorotetradecyl acrylate, perfluorotetradecyl methacrylate, perfluorohexadecyl acrylate, perfluorohexadecyl methacrylate, perfluorooctadecayl acrylate, and perfluorooctadecayl methacrylate. Perfluorohexyl acrylate, perfluorooctyl acrylate, and perfluorodecyl acrylate are preferred.

[0027] 2. Organic solvents The water-repellent protective film composition of this invention is prepared in liquid form by thoroughly mixing the components of the support layer and the water-repellent layer with a solvent. The amount of solvent significantly affects the film-forming effect. The solid content (i.e., the support layer and water-repellent layer components, excluding solvent) is preferably controlled between 30-80% by weight, based on the total weight of the composition. Within this range, it ensures suitable coating fluidity, guaranteeing uniform spreading on the semiconductor substrate surface, while maintaining the dispersion stability of the support layer and water-repellent layer materials. For example, when the support layer uses a blend of low-polymerization and high-polymerization polycaprolactone, too low a solid content may lead to insufficient mechanical strength of the film; too high a content will result in excessively high solution viscosity, affecting its penetration and filling effect in high aspect ratio structures. For the fluorinated acrylate compound in the water-repellent layer, an appropriate solid content helps form a continuous, dense, nanoscale rough structure, ensuring low surface energy water-repellent properties.

[0028] Regarding solvent selection, this invention exhibits broad applicability. The core requirement is that the solvent must be able to fully dissolve all components of the support layer and water-repellent layer, and possess chemical stability to avoid adverse reactions with the materials. More specific examples of solvents include: methanol, ethanol, tetrahydrofuran, dioxane, methyl cellosolve acetate, ethyl cellosolve acetate, ethyl acetoacetate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, dipropylene glycol diethyl ether, propylene glycol dimethyl ether, dipropylene glycol diethyl ether, propylene glycol dimethyl ether, ...methyl ether, propylene glycol diethyl ether, propylene glycol dimethyl ether, propylene glycol dimethyl ether, propylene glycol dimethyl ether, propylene glycol dimethyl ether, propylene glycol dimethyl ether, propylene glycol dimethyl ether, propylene Methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol butyl ether acetate, toluene, xylene, methyl ethyl ketone, 4-hydroxy-4-methyl-2-pentanone, cyclopentanone, cyclohexanone, 2-heptanone, γ-butyrolactone, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, etc.

[0029] To ensure good solubility, the preferred solvents are: propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, dipropylene glycol methyl ether acetate, and propylene glycol butyl ether acetate.

[0030] 3. Regarding the water-repellent protective membrane with composite structure In this invention, the composite-structured water-repellent protective film is a functional film layer that significantly reduces the wettability of substrate surfaces and endows them with excellent water-repellent properties by constructing a molecular-level composite structure on the surface of substrates such as wafers. This protective film is composed of a support layer and a surface water-repellent layer working together. The materials of each layer are specifically designed and synthesized to achieve surface energy reduction and enhanced water-repellent effect from different levels.

[0031] 4. Regarding chips Generally, to obtain a wafer with a surface featuring fine bumps and depressions, firstly, a photoresist is coated onto a smooth wafer surface. Then, the photoresist is exposed through a photoresist mask, and the exposed or unexposed photoresist is etched away, thereby creating a photoresist layer with the desired bump and depression pattern. Alternatively, a photoresist layer with a bump and depression pattern can also be obtained by pressing a patterned mold against the photoresist layer. Next, the wafer is etched. At this time, the wafer surface corresponding to the recesses in the photoresist pattern is selectively etched. Finally, by peeling off the photoresist layer, a wafer with fine bump and depression patterns is obtained.

[0032] 5. Regarding the surface treatment of wafers In this invention, the cleaning method for the wafer is not particularly limited as long as a cleaning device capable of maintaining the aforementioned liquid state on the raised and recessed patterns of the wafer is used. Examples of wafer cleaning methods include: single-wafer cleaning, which employs a rotary cleaning device. By keeping the wafer horizontally rotated and supplying cleaning fluid towards the center, centrifugal force is used to evenly cover the wafer surface with the cleaning fluid. This method allows for precise control of the contact time and intensity between the cleaning fluid and the film layer, avoiding damage to the support layer and the hydrophobic layer. The support layer is composed of a blend of materials with different degrees of polymerization. The low-polymerization-degree material provides good fluidity, while the high-polymerization-degree material provides mechanical strength. The gentle action of rotary cleaning prevents damage to the support layer structure due to external forces, ensuring its stable support for the circuit pattern. Simultaneously, rotary cleaning maintains the low surface energy hydrophobic properties of the hydrophobic layer. If batch cleaning is used, when immersing multiple wafers in the cleaning tank, the flow rate and direction of the cleaning fluid must be strictly controlled to prevent collisions between wafers, which could cause rupture of the support layer film or wear on the surface of the hydrophobic layer, affecting the overall protective performance.

[0033] The drying process is crucial to the final performance of the protective film. Rotary drying uses centrifugal force to remove surface liquid, resulting in rapid drying without thermal damage. This method is suitable for mechanically sensitive support layer materials, preventing structural deformation. IPA vapor drying utilizes the volatility and low surface tension of isopropanol to effectively remove residual liquid from tiny depressions without damaging the nanoscale rough structure of the water-repellent layer, ensuring its water-repellent properties. During the drying process, the temperature must be controlled according to the thermal stability of the material to prevent the degradation or structural rearrangement of heat-sensitive materials in the support and water-repellent layers due to high temperatures, ensuring that the water-repellent film performs excellent protective functions in fields such as semiconductor manufacturing.

[0034] The present invention will now be described in more detail through embodiments; however, these examples are provided to illustrate the invention, and the scope of the invention is not limited thereto. In the following embodiments, the methods for detecting each performance indicator are as follows: (1) Determination of weight-average molecular weight: The determination was performed using gel permeation chromatography (GPC) with polystyrene standards.

[0035] (2) Evaluation of the contact angle of the protective film formed on the wafer surface: Approximately 2 μL of pure water was placed on the surface of a wafer with a protective film, and the angle (contact angle) between the water droplet and the wafer surface was measured using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd.: CA-X type).

[0036] (3) Fill rate test: First, analog circuit trench structures with a specified aspect ratio are fabricated on a silicon wafer. After coating and curing a protective film, cross-sectional samples are obtained by focused ion beam cutting. Field emission scanning electron microscopy (FESEM) is used to observe the sample cross-section. High-resolution images are captured at multiple locations, and quantitative analysis is performed using image processing software. The formula for calculating the fill rate (η) is: η = (Afilled / Atotal) × 100%, where Afilled represents the pixel area of ​​the filled region in the SEM image, and Atotal represents the total pixel area of ​​the trench structure. To verify the accuracy of the results, X-ray reflectance or confocal microscopy can be used for three-dimensional morphology detection. The ambient temperature must be controlled at 23±1℃ during the testing process, and repeated measurements should be performed at the same location to ensure data reliability. This method can objectively evaluate the filling performance of the protective film for fine structures, providing a basis for material optimization.

[0037]

[0038] S1, Synthetic polycaprolactone oligomers All synthetic raw materials, catalysts, solvents, and experimental equipment used must undergo rigorous drying before the experiment. Under nitrogen protection, 100.0 g of ε-caprolactone, 250 ml of anhydrous toluene, 1.35 g of benzyl alcohol (the initiator in the reaction), and 0.154 g of stannous octoate were added to the reaction flask. The reaction flask was placed in an oil bath at 120℃±3℃ and reacted for 10 hours under nitrogen atmosphere and magnetic stirring. After the reaction was completed, the mixture was cooled to room temperature and quenched with a small amount of glacial acetic acid / ethanol. Then, the precipitate was rapidly added dropwise to glacial methanol, allowed to stand, filtered, and the precipitate was washed several times with methanol. The product was then dried under vacuum at 40℃ to constant weight to obtain approximately 99 g of white solid. GPC (Gross Polystyrene Weight Average Molecular Weight, the same below) showed that its Mw was approximately 8100 and its PDI was approximately 1.10.

[0039] S2, Synthetic polycaprolactone polymer All synthetic raw materials, catalysts, solvents, and experimental equipment used must undergo rigorous drying before the experiment. Under nitrogen protection, 100.0 g of ε-caprolactone, 350 ml of anhydrous toluene, 0.831 g of benzyl alcohol, and 0.094 g of stannous octoate were added to the reaction flask. The reaction flask was placed in an oil bath at 120℃±3℃ and reacted for 24 hours under nitrogen atmosphere and magnetic stirring. After the reaction was completed, the mixture was cooled to room temperature, and the reaction was quenched with a small amount of glacial acetic acid / ethanol. The precipitate was then rapidly precipitated by adding it dropwise to glacial methanol. After standing and filtration, the precipitate was washed several times with methanol. The product was then dried under vacuum at 40℃ to constant weight to obtain approximately 99 g of a white waxy solid. GPC analysis showed its Mw to be approximately 13300 and PDI to be approximately 1.18.

[0040] S3, polycaprolactone polymer grafted with perfluorohexyl acrylate All raw materials, catalysts, solvents, and experimental equipment used in the synthesis must be strictly dried before the experiment. Under nitrogen protection, 93.0 g of PCL-OH synthesized by S2 was added to the reaction flask, followed by 300 ml of anhydrous dichloromethane solvent and stirring to dissolve. The mixture was then heated to 0°C in an ice-water bath, and 1.3 g of triethylamine catalyst was slowly added dropwise while stirring for 10 min. 2.1 g of 2-bromoisobutyryl bromide was then slowly added dropwise. After the addition was completed, the mixture was heated to room temperature and reacted for 24 h. After the reaction was completed, the triethylamine bromide was removed by filtration, the mixture was concentrated by rotary evaporation, precipitated three times with ice-cold methanol, and dried under vacuum at 40°C to constant weight to obtain PCL-Br.

[0041] All synthetic raw materials, catalysts, solvents, and experimental equipment used must undergo rigorous drying before the experiment. Then, under nitrogen protection, 93.0 g of the synthesized PCL-Br, 7.0 g of perfluoroethyl acrylate, and 300 ml of a 1:1 mixture of toluene and trifluorotoluene were added to the reaction flask and stirred to dissolve. The mixture was deoxygenated three times by freeze-drying. Then, 0.52 g of the catalyst CuBr and 0.63 g of the catalyst ligand PMDETA were added, followed by stirring in an oil bath at 65°C for 10 h. After the reaction was complete, a small amount of methanol was added to quench the reaction. Subsequently, the copper salt catalyst was removed by passing the mixture through a neutral alumina column. The mixture was concentrated by rotary evaporation, precipitated by dripping with ice-cold methanol, filtered, and repeated three times. The mixture was then dried under vacuum at 40°C to constant weight to obtain approximately 89 g of PCL-g-PFA, a white waxy solid. GPC analysis showed its Mw to be approximately 14000 and its PDI to be approximately 1.23.

[0042] Example 1

[0043] Accurately weigh 10g of polycaprolactone oligomer prepared in synthesis example S1, 10g of PCL-OH prepared in synthesis example S2, and 10g of PCL-g-PFA prepared in synthesis example S3, and dissolve them in an appropriate amount of propylene glycol methyl ether acetate. Use a magnetic stirrer to stir at room temperature until completely dissolved to obtain a protective film composition solution with a solid content of 20%. Use a pipette to draw the solution and drop it onto the center of a semiconductor substrate fixed to the sample stage of a spin coater. Set the spin coater speed to 800 rpm and the time to 30 seconds to complete the coating in a clean environment. After coating, dry under reduced pressure of 100 Pa, and then place it on a hot plate at 120℃ for 1 hour to cure the protective film.

[0044] Example 2

[0045] Accurately weigh 5g of polycaprolactone oligomer prepared in synthesis example S1, 12.5g of PCL-OH prepared in synthesis example S2, and 12.5g of PCL-g-PFA prepared in synthesis example S3, and dissolve them in an appropriate amount of propylene glycol methyl ether acetate. Use a magnetic stirrer to stir at room temperature until completely dissolved to obtain a protective film composition solution with a solid content of 20%. Use a pipette to drop the solution onto the center of a semiconductor substrate fixed on the sample stage of a spin coater. Set the spin coater speed to 800 rpm and the time to 30 seconds to complete the coating in a clean environment. After coating, dry under reduced pressure of 100 Pa, and then place it on a hot plate at 120℃ for 1 hour to cure the protective film.

[0046] Example 3

[0047] Accurately weigh 12.5g of polycaprolactone oligomer prepared in synthesis example S1, 12.5g of PCL-OH prepared in synthesis example S2, and 5g of PCL-g-PFA prepared in synthesis example S3, and dissolve them in an appropriate amount of propylene glycol methyl ether acetate. Use a magnetic stirrer to stir at room temperature until completely dissolved to obtain a protective film composition solution with a solid content of 20%. Use a pipette to draw the solution and drop it onto the center of a semiconductor substrate fixed on the sample stage of a spin coater. Set the spin coater speed to 800 rpm and the time to 30 seconds to complete the coating in a clean environment. After coating, dry under reduced pressure of 100 Pa, and then place it on a hot plate at 120℃ for 1 hour to cure the protective film.

[0048] Example 4

[0049] Accurately weigh 0g of polycaprolactone oligomer prepared in synthesis example S1, 15g of PCL-OH prepared in synthesis example S2, and 15g of PCL-g-PFA prepared in synthesis example S3. Dissolve them in an appropriate amount of propylene glycol methyl ether acetate. Use a magnetic stirrer to stir at room temperature until completely dissolved to obtain a protective film composition solution with a solid content of 20%. Use a pipette to drop the solution onto the center of a semiconductor substrate fixed to the sample stage of a spin coater. Set the spin coater speed to 800 rpm and the time to 30 seconds to complete the coating in a clean environment. After coating, dry under reduced pressure of 100 Pa and then place it on a hot plate at 120℃ for 1 hour to cure the protective film.

[0050] Comparative Example 5: The sample preparation conditions were the same as in Example 1, except that the sample was prepared using the added synthetic example S3, and the grafted perfluorohexyl acrylate was replaced with grafted perfluorooctyl acrylate.

[0051] Table 1

[0052] As can be seen from the performance results in Table 1, the water-repellent protective film based on the composite structure has an interdependent and synergistic effect between the surface water-repellent layer and the support layer, which together endow the protective film with excellent water repellency, high filling rate and reliable support capability. The rational design and precise preparation of each layer of material are the key to achieving a high-performance protective film. Any missing or insufficient performance of any layer will lead to a significant decrease in the overall performance of the protective film, which will not be able to meet the stringent requirements for wafer protection in high-end fields such as semiconductor manufacturing.

[0053] The innovation of this invention lies in providing a water-repellent protective membrane with a composite structure. This membrane employs a composite design of a support layer and a surface water-repellent layer, achieving superior comprehensive protective performance through material synergy. The support layer utilizes a gradient polymerization technique, where low-polymerization-degree components permeate through nanoscale pores to achieve efficient filling of a high aspect ratio structure, while high-polymerization-degree components enhance the support stability for microcircuit patterns on the wafer. The surface water-repellent layer is grafted with perfluoroacrylate, exhibiting ultra-low surface energy and a water contact angle ≥110°. This invention addresses the shortcomings of single-material performance through structural synergy.

[0054] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A composite water-repellent protective membrane, comprising a support layer and a water-repellent layer disposed on the surface of the support layer, wherein: (1) The support layer comprises a low-polymerization degree material (Ⅰ) and a high-polymerization degree material (Ⅱ). A-(B) i -C (Ⅰ) In structural formula (Ⅰ), B is a repeating unit selected from polycaprolactone segment (CH2)5−CO−O, polylactic acid segment CH(CH3)−CO−O, and polycarbonate segment O−C(=O)−O−R, where R is selected from aliphatic or aromatic groups; A and C are the head and tail groups of the molecular chain, selected from hydroxyl, carboxyl, amino, or methyl and ethyl groups; the degree of polymerization i ranges from 1 to 50. A-(B) m -C (Ⅱ) In structural formula (II), B is a repeating unit selected from polycaprolactone segment (CH2)5−CO−O, polylactic acid segment CH(CH3)−CO−O, and polycarbonate segment O−C(=O)−O−R, where R is selected from aliphatic or aromatic groups; A and C are the head and tail groups of the molecular chain, selected from hydroxyl, carboxyl, amino, or methyl and ethyl groups; the degree of polymerization m ranges from 51 to 200. (2) The water-repellent layer is obtained by grafting water-repellent monomers onto a high-polymerization-degree material (II), wherein the water-repellent monomers are selected from: perfluorohexyl acrylate, perfluorohexyl methacrylate, perfluorooctyl acrylate, perfluorooctyl methacrylate, perfluorodecyl acrylate, perfluorodecyl methacrylate, perfluorododecyl acrylate, perfluorododecyl methacrylate, perfluorotetradecyl acrylate, perfluorotetradecyl methacrylate, perfluorohexadecyl acrylate, perfluorohexadecyl methacrylate, perfluorooctadecyl acrylate, and perfluorooctadecyl methacrylate.

2. The water-repellent protective membrane with a composite structure according to claim 1, characterized in that: The water-repellent monomer is selected from perfluorohexyl acrylate, perfluorooctyl acrylate, and perfluorodecyl acrylate.

3. The water-repellent protective membrane with a composite structure according to claim 1, characterized in that: The repeating units in the low-polymerization-degree material (Ⅰ) and the high-polymerization-degree material (Ⅱ) are selected from polycaprolactone segments (CH2)5−CO−O.

4. The water-repellent protective membrane with the composite structure according to claim 1, characterized in that: The mass ratio of the low-polymerization-degree material (Ⅰ) to the high-polymerization-degree material (Ⅱ) ranges from 24:75 to 60:

40.

5. A method for preparing a water-repellent protective membrane with a composite structure according to any one of claims 1-4, characterized in that... Includes the following steps: S1. Synthesis of polycaprolactone oligomers: Under nitrogen protection, ε-caprolactone monomer, organic solvent, initiator, and catalyst were added to a reaction flask. The reaction flask was placed in an oil bath at 120℃±3℃ and reacted for 8-15 hours under nitrogen atmosphere and magnetic stirring. After the reaction was completed, the mixture was cooled to room temperature and the reaction was quenched with a small amount of glacial acetic acid / ethanol. Then, the mixture was rapidly added dropwise to glacial methanol to precipitate the product. After standing and filtering, the precipitate was washed with methanol several times and dried to obtain a white solid polycaprolactone oligomer. The molar ratio of ε-caprolactone monomer to initiator was (55-75):

1. S2. Synthesis of polycaprolactone polymer: Under nitrogen protection, ε-caprolactone monomer, organic solvent, initiator and catalyst were added to the reaction flask; the reaction flask was placed in an oil bath at 120℃±3℃ and reacted for 8-15 hours under nitrogen atmosphere and magnetic stirring. After the reaction was completed, the mixture was cooled to room temperature and the reaction was quenched with a small amount of glacial acetic acid / ethanol. Then, the precipitate was rapidly added dropwise to glacial methanol, allowed to stand, filtered, and the precipitate was washed with methanol several times and dried to obtain a white solid polycaprolactone polymer; the molar ratio of ε-caprolactone monomer to initiator was (90-110):1; S3. Synthesis of the water-repellent polymer: Under nitrogen protection, the polycaprolactone polymer and solvent were added to the reactor and stirred to dissolve. After stirring, the mixture was placed in an ice-water bath. The catalyst and bromine source were slowly added under stirring. After the addition was completed, the temperature was raised to 25±5℃ and the reaction was carried out for more than 12 hours. After the reaction was completed, the triethylamine bromide was removed by filtration. Then, the mixture was concentrated by rotary evaporation, precipitated with ice-cold methanol, and dried to obtain PCL-Br. S4. Under nitrogen protection, PCL-Br, water-repellent monomer and solvent are added to the reactor and stirred to dissolve. After deoxygenation by freeze pumping, catalyst is added and the reaction is stirred at 65±5℃ for at least 8 hours. After the reaction is completed, quencher is added to quench the reaction and catalyst is removed by passing through a neutral alumina column. After rotary evaporation and concentration, ice-cold methanol is added dropwise to precipitate and filter. The water-repellent layer material is then dried. S5. Weigh out polycaprolactone oligomer, polycaprolactone polymer, and water-repellent layer material in a molar ratio of (0.9-1.2):(0.9-1.2):(0.9-1.2), dissolve them in a solvent, and stir until completely dissolved to obtain a protective film composition solution. S6. The protective film composition solution is dropped onto the semiconductor substrate and spin-coated. After drying under reduced pressure, the protective film is cured and formed.

6. The method for preparing the composite water-repellent protective membrane according to claim 5, characterized in that: In steps S1 and S2, which synthesize polycaprolactone oligomers and polycaprolactone polymers respectively, the initiator is selected from monohydroxy initiators, dihydroxy initiators, or polyhydroxy initiators. The monohydroxy initiators include methanol, ethanol, isopropanol, tert-butanol, n-hexanol, and benzyl alcohol. The dihydroxy initiators include ethylene glycol, 1,3-propanediol, 1,4-butanediol, dihexanediol, and terephthalic acid. The polyhydroxy initiators include glycerol, trimethylolpropane, pentaerythritol, and glucose, etc. A monohydroxy initiator is preferred.

7. The method for preparing the composite water-repellent protective membrane according to claim 5, characterized in that: In steps S1 and S2, the organic solvent is selected from anhydrous toluene, the catalyst is selected from stannous octoate, and the quencher is selected from glacial acetic acid and / or ethanol.

8. The method for preparing the composite water-repellent protective membrane according to claim 5, characterized in that: In step S3, the solvent is selected from anhydrous dichloromethane and the bromine source is selected from 2-bromoisobutyryl bromide.

9. The method for preparing the composite structure water-repellent protective membrane according to claim 5, characterized in that: In step S4, the solvent is composed of toluene and trifluorotoluene in a volume ratio of 1:1; the catalyst is copper bromide CuBr and N,N,N',N'',N''-pentamethyldiethylenetriamine PMDETA.

10. The method for preparing the composite structure water-repellent protective membrane according to claim 5, characterized in that: The solvent in step S5 is selected from: methanol, ethanol, tetrahydrofuran, dioxane, methyl cellosolve acetate, ethyl cellosolve acetate, ethyl acetoacetate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, dipropylene glycol diethyl ether, propylene glycol monomethyl ... Methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol butyl ether acetate, toluene, xylene, methyl ethyl ketone, 4-hydroxy-4-methyl-2-pentanone, cyclopentanone, cyclohexanone, 2-heptanone, γ-butyrolactone, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone.

11. The method for preparing the composite water-repellent protective membrane according to claim 10, characterized in that: In step S5, the solvent is selected from propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, dipropylene glycol methyl ether acetate, and propylene glycol butyl ether acetate.

Citation Information

Patent Citations

  • Surface preparation agent and surface treatment method

    JP2017063179A